Traditional Chinese medicine on treating myelosuppression after chemotherapy: A protocol for systematic review and meta-analysis. Issue 4 (29th January 2021) - Yang, Sihang; Che, Hong; Xiao, Li; Zhao, Bingjie; Liu, Songshan
Abstract: Background: Myelosuppression after chemotherapy is a common adverse reaction in the process of chemotherapy, mainly manifested as anemia, increased risk of bleeding, infection, the results seriously affect the quality of life and prognosis of patients, become the main cause of death. Since ancient times, traditional Chinese medicine (TCM) has been widely used in East Asia (such as China, Japan, South Korea) in the clinical treatment of bone marrow suppression after chemotherapy, which plays the role of synergism, toxicity reduction, immune regulation, and gradually developed into an indispensable role. Therefore, the purpose of this study was to use a network meta-analysis to evaluate the evidence that traditional Chinese medicine is related to the efficacy and safety of chemotherapy-induced myelosuppression. Methods: This study will search the following Chinese and English databases electronically: 4 Chinese literature databases, including China biology and medicine database, China National Knowledge Infrastructure, VIP, and Wan fang database, and 3 British literature databases including PubMed, EMBASE, and Cochrane Library. The search keywords were (traditional Chinese medicine or medicinal plants or extracts of traditional Chinese medicine or traditional Chinese medicine formula or preparation) and (myelosuppression after chemotherapy) and (randomized controlled trials) (RCTs). The search time limit is set to December 2020, and Chinese and English languages will be included. The included subjects must be diagnosed with myelosuppression after chemotherapy and RCTs should be conducted at the same time. The main outcome was elevated hemoglobin, platelets, leukocytes, and neutrophils. The secondary results were reticulocyte absolute value, reticulocyte percentage, low-fluorescence reticulocyte red, medium-fluorescent reticulocyte red, and high-fluorescence reticulocyte red. We will conduct a risk and quality assessment of the included studies using the Cochrane tool, and carefully calculate data synthesis after meta-analysis using Rev Man software (version 5.3.5) and R software (version 3.6.1). Results: The study is aim to evaluate the efficacy and safety of the treatment that traditional Chinese medicine for myelosuppression after chemotherapy. Conclusion: This study of the meta-analysis could provide evidence for clinicians and help patients to make a better choice. INPLASY registration number: INPLASY2020120097